Optimization of Low Site Density Area for 4G Network in Urban City - Hajiar Yuliana; Sofyan Basuki; Salita Ulitia Prini (National Research and Innovation Agency, 2021)
The development of telecommunications is currently growing rapidly, especially in urban areas. To obtain optimal data services for users, the performances of 4G network services must continue to be optimized. It is known that many users are scattered in urban areas, but sometimes it is not balanced with an even distribution of the site in this area. This condition occurs because the distribution of the site is not evenly optimal distributed, either due to licensing constraints, limited land access for site development, or in terms of plans that have not been made. Balanced with the requirement of a 4G network, which is required, this